(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The second part of the XXth. century was marked by an increasing interest towards the literature of the Elizabethan Аge. The repesentatives of world countries devoted their investigations to the works of fiction written in the time of Renaissanse. Owing to their works the names of Th. Lodge, R. Greene, N. Breton and etc. became known among the modern scientists who are interested in the literature of the XVIth. century. Thematically the set of Th. Nashe’s works have their peculiarities. They are the following: the themes are interconnected, they are repeated from pamphlet to novel, from drama to poem, some themes are so-called penetrating through all his works. There are some problematic aspects typical of him and some concepts, which are traditional for his works dependless of a genre. The given article also insists on existing some identical poetological details in his different works, but they are obligatory united by the patriotic imperative. Finally, the article declares that Nashe is famous for his particular style, which is characterised by combinability of “the new” and “the old”. The author of the given article comes to coclusion that the results of this panoramic investigation in future would be very useful for those scholars, who will deepen into the specific character of his works taken separately, but on the whole.